Indonesian pharmacists' and pharmacy students' attitudes towards collaboration with physicians - Setiadi AP; Wibowo Y; Irawati S; Setiawan E; Presley B; Gudka S; Wardhani AS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Background: Recent implementation of national health coverage and the increasing health burden in Indonesia require health professionals, including pharmacists, to work more collaboratively to improve access and quality of health care. Nevertheless, relatively little is known about Indonesian pharmacists' attitude towards collaboration. Objective: To assess and compare the attitude of Indonesian pharmacy students and pharmacists towards collaboration with physicians. Methods: A survey of 95 pharmacy students (Universitas Surabaya) and 114 pharmacists (public health facilities in East Java) in Indonesia was conducted using the validated questionnaire, Scale of Attitudes Toward Physician-Pharmacist Collaboration (SATP2C), which was translated in Bahasa Indonesia. The questionnaire contained 16 items which were based on a 4-point Likert scale. Descriptive statistics were used to summarise the responses, (i.e., individual scores, factor scores and total scores). Results: Response rates of 97.9% and 65.8% were reported for students and pharmacists, respectively. The mean total score of SATP2C among Indonesian students and pharmacists were 56.53 versus 56.77, respectively; indicating positive attitudes toward collaboration. Further analysis of each item of SATP2C confirmed the positive attitudes in which mean and median scores of ≥3 were reported for most items in both groups. Significant differences between students and pharmacists were found regarding the following items: (i) 'there are many overlapping areas of responsibility between pharmacists and physicians' (3.28 versus 2.89, respectively; p<0.001), (ii) 'pharmacist should clarify a physician's order' (3.54 versus 3.71, respectively; p=0.046); and (iii) 'physicians should consult with pharmacists about adverse reactions or refractory to drug treatment' (3.60 versus 3.44, respectively; p=0.022). Conclusions: Indonesian pharmacists reported positive attitudes toward collaboration with physicians. Further research is needed to understand other factors contributing in translating those positive attitudes into actual practice, and thus, providing a good foundation for policy makers, researchers and practitioners to support pharmacist-physician collaboration in Indonesia.